2014
DOI: 10.4161/epi.28864
|View full text |Cite
|
Sign up to set email alerts
|

SETD6 controls the expression of estrogen-responsive genes and proliferation of breast carcinoma cells

Abstract: The lysine methyltransferase SETD6 modifies the histone variant H2AZ, a key component of nuclear receptor-dependent transcription. Herein, we report the identification of several factors that associate with SETD6 and are implicated in nuclear hormone receptor signaling. Specifically, SETD6 associates with the estrogen receptor α (ERα), histone deacetylase HDAC1, metastasis protein MTA2, and the transcriptional co-activator TRRAP. Luciferase reporter assays identify SETD6 as a transcriptional repressor, in agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…Very little is known about the remaining SET proteins, although amplification of ASH1L was recently reported in over 10% of breast cancers (Liu et al., 2015). Intriguingly, knockdown of both SETD4 (Faria et al., 2013) and SETD6 (O'Neill et al., 2014) significantly suppressed proliferation of breast cancer cell lines, suggesting they may have pro‐proliferative functions.…”
Section: Introductionmentioning
confidence: 99%
“…Very little is known about the remaining SET proteins, although amplification of ASH1L was recently reported in over 10% of breast cancers (Liu et al., 2015). Intriguingly, knockdown of both SETD4 (Faria et al., 2013) and SETD6 (O'Neill et al., 2014) significantly suppressed proliferation of breast cancer cell lines, suggesting they may have pro‐proliferative functions.…”
Section: Introductionmentioning
confidence: 99%
“…Lysine methylation, catalyzed by protein lysine methyltransferases (PKMTs), is a PTM that plays a key role in a variety of essential cellular signaling pathways (14). In recent years, the PKMT SETD6 has been shown to participate in the NF-κB cascade (15,16), the nuclear factor erythroid 2-related factor 2 (NRF2) oxidative stress response (17), the Wnt signaling pathway (18), nuclear hormone receptor signaling (19), and embryonic stem cell differentiation (20), all of which are vital cellular processes.…”
mentioning
confidence: 99%
“…SETD6 is a mono-methyltransferase that directly methylates RelA at Lys-310 to suppress the activation of NF-B target genes. It was recently shown that mono-methylation of H2AZ by SETD6 at lysine 7 is required for the maintenance of embryonic stem cell self-renewal (11) and that SETD6 associates with several factors that control the expression of estrogenresponsive genes in the nuclear hormone receptor signaling pathway (12).…”
mentioning
confidence: 99%